2020
DOI: 10.3390/ijerph17228657
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing Nature to Satisfy Basic Psychological Needs in Parenting: A Quasi-Experiment in Family Shelters

Abstract: Finding fulfillment of basic psychological needs may be difficult for parents living in shelters after becoming homeless or after escaping violence. This study tested if experiencing nature was associated with the basic psychological needs of parents in shelters. Need satisfaction and need frustration were measured among parents in shelters (N = 160), with one measurement in the standard indoor context of the shelter and one measurement while experiencing nature. Experiencing nature was associated with enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Of the thirteen reviewed studies, ten explicitly addressed relationships between safety and security and the design of the built environment. It should be noted that papers that did not directly address issues of safety and security had a targeted emphasis on health and wellbeing, including the role of gardens and the natural environment [ 52 , 53 ] and community spaces [ 21 ]. Two themes were identified encompassing defensible environments [ n = 9] and environmental stressors [ n = 8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the thirteen reviewed studies, ten explicitly addressed relationships between safety and security and the design of the built environment. It should be noted that papers that did not directly address issues of safety and security had a targeted emphasis on health and wellbeing, including the role of gardens and the natural environment [ 52 , 53 ] and community spaces [ 21 ]. Two themes were identified encompassing defensible environments [ n = 9] and environmental stressors [ n = 8].…”
Section: Resultsmentioning
confidence: 99%
“…Under the first theme, the natural environment was the exclusive focus of three papers in this scoping review [ 48 , 52 , 53 ], underscoring the role of nature as a therapeutic setting and the benefits of direct interaction with flora and fauna. In their quantitative study of parents living in shelters, Peters et al demonstrated that direct connections with nature significantly affected psychological need fulfilment [ 53 ] and was associated with higher parental need satisfaction and lower parental need frustration, particularly for parents with young children [ 52 ]. Huffman [ 21 ], discussing the role of community spaces in supporting wellbeing in permanent supportive housing, describes how the food garden offers both peace and quiet, as well as positive childhood memories for some residents.…”
Section: Resultsmentioning
confidence: 99%
“…Visiting a natural environment such as a garden, children’s farm, a forest, or park can be supportive to families. Studies in shelters as well as in other living places have indicated that natural environments near a family’s living place can be used as a safe and engaging place for family activities, where parents can find fun and unconstrained ways to interact with their children ( Ashbullby et al, 2013 ; Izenstark et al, 2016 , 2021 ; Cameron-Faulkner et al, 2018 ; Millican et al, 2019 ; Kotozaki, 2020 ; Rantala and Puhakka, 2020 ; Peters et al, 2020a ; Varning Poulsen et al, 2020 ). Such positive moments in nature are associated with stress reduction in parents ( Razani et al, 2018 ; Kotozaki, 2020 ) and responsive interactions between parent and child ( Cameron-Faulkner et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such positive moments in nature are associated with stress reduction in parents ( Razani et al, 2018 ; Kotozaki, 2020 ) and responsive interactions between parent and child ( Cameron-Faulkner et al, 2018 ). For parents in shelters specifically, experiences in a natural environment have been associated with parents’ experiences of connectedness with their child, autonomy in making parenting decisions, and competence in their parenting practice ( Peters et al, 2020a , b , 2021 ). These findings suggest that professionals may use engagement with nature to support parents in shelters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation